Physical Chemistry from a Different Angle Workbook Exercises and Solutions - Job, Georg; Rüffler, Regina (Springer International Publishing : Imprint: Springer, 2019)
As a companion to the undergraduate textbook "Physical Chemistry from a Different Angle", this workbook offers an excellent opportunity to deepen the understanding of the concepts presented in the textbook by addressing specific problems. The workbook is divided into two parts: a first part with nearly 200 exercises and a second part providing the corresponding detailed solutions with helpful comments, enabling students to learn independently.